Implementasi Pijat Oksitosin dalam Upaya Peningkatan Produksi ASI di Klinik Afisya Kabupaten Deli Serdang Provinsi Sumatera Utara Tahun 2025 - Marta A.Silaban; Eva D. Sinaga; Erin P. Siregar; Novita A.Manjorang; Ade Rachmat; Sri Aisyah (Lembaga Pengembangan Kinerja Dosen, 2025)
In order to improve the welfare of the community, it is expected that the government will also participate in improving health standards, especially for mothers. This is because healthy mothers will produce superior generations. The best food for babies is breast milk, therefore it is expected that mothers can give their babies exclusive breast milk so that the baby's growth and development are optimal and grow into a healthy, intelligent and productive adult generation. Breastfeeding itself also has obstacles including sore nipples, babies who often cry. Oxytocin massage aims to increase breast milk production in mothers in labor. The implementation of this community service is aimed at prospective breastfeeding mothers and breastfeeding mothers. This activity took place at the Afisya Clinic, Deli Serdang Regency, North Sumatra Province. The method of implementing assistance and application of oxytocin massage consists of refreshing the knowledge and skills of midwives in implementing oxytocin massage. The results of this community service can improve the knowledge and skills of midwives in implementing oxytocin massage. There was an increase in midwives' knowledge by 53% and skills by 100% and all mothers in labor gave breast milk to their mothers. It is hoped that the implementation of oxytocin massage will be applied to all mothers giving birth so that mothers can provide exclusive breastfeeding.